Spatial regulation of greatwall by Cdk1 and PP2A-Tws in the cell cycle. Issue 4 (16th February 2016) - Wang, Peng; Larouche, Myreille; Normandin, Karine; Kachaner, David; Mehsen, Haytham; Emery, Gregory; Archambault, Vincent
ABSTRACT: Entry into mitosis requires the phosphorylation of multiple substrates by cyclin B-Cdk1, while exit from mitosis requires their dephosphorylation, which depends largely on the phosphatase PP2A in complex with its B55 regulatory subunit (Tws in Drosophila). At mitotic entry, cyclin B-Cdk1 activates the Greatwall kinase, which phosphorylates Endosulfine proteins, thereby activating their ability to inhibit PP2A-B55 competitively. The inhibition of PP2A-B55 at mitotic entry facilitates the accumulation of phosphorylated Cdk1 substrates. The coordination of these enzymes involves major changes in their localization. In interphase, Gwl is nuclear while PP2A-B55 is cytoplasmic. We recently showed that Gwl suddenly relocalizes from the nucleus to the cytoplasm in prophase, before nuclear envelope breakdown and that this controlled localization of Gwl is required for its function. We and others have shown that phosphorylation of Gwl by cyclin B-Cdk1 at multiple sites is required for its nuclear exclusion, but the precise mechanisms remained unclear. In addition, how Gwl returns to its nuclear localization was not explored. Here we show that cyclin B-Cdk1 directly inactivates a Nuclear Localization Signal in the central region of Gwl. This phosphorylation facilitates the cytoplasmic retention of Gwl, which is exported to the cytoplasm in a Crm1-dependent manner. In addition, we show that PP2A-Tws promotes the return of Gwl to its nuclear localization during cytokinesis. Our results indicate that the cyclic changes in Gwl localization at mitotic entry and exit are directly regulated by the antagonistic cyclin B-Cdk1 and PP2A-Tws enzymes.